Sistem Kontrol Posisi Parkir Mundur Pada Prototipe Mobil Listrik - Dwi Supiyantoro; Peby Wahyu Purnawan (MAESTRO, 2019)
ABSTRACT In this final project a reverse parking position control system has been designed on an electric car prototype when moving backwards. The system parts consist of one car miniature unit, LCD, ultrasonic sensor, braking system, switch, and servo motor as an actuator, for the controller used Arduino ATMega 2560. When the car moves backward the ultrasonic sensor will read the distance of the car with the object behind it and from the distance reading the car's movement speed is calculated. The results of the distance reading and speed calculation are displayed on the display screen. To avoid the collision of the car with the object behind it, the distance reading and calculation of the speed of the car besides being displayed on the display are also used as input to the microcontroller on Arduino ATMega 2560 to control the position of the car with automatic motor speed and braking when the car reaches a certain distance to the object in behind him. Tested on this system to determine the effectiveness of the reverse parking position control system on this electric car prototype in avoiding the car hitting the object behind it. From the results of the tests conducted, the speed of the car decreases when the distance to the object behind it is 50 cm and stops at the position of the car to the object behind 8 to 9 cm, proving that the parking position control system on the electric car prototype can avoid collision with the object behind it when moving backwards. Keywords: automatic braking, car, parking, ultrasonic, servo.